PENERAPAN NILAI PENDIDIKAN ISLAM DI SDN CIMANGGU 03 CIBUNGBULANG BOGOR - Siti Asy Syifa; Suyud Arif; Syarifah Gustiawati (Al-Mubin, 2023)
The importance of Islamic religious education in primary schools lies in the education of the younger generation. Basically, Islamic religious education aims to increase faith, understanding, and practice in Islam so that students become students who believe and fear Allah SWT and have a noble character in personal, social, national, and state life. Therefore, it is very important to apply the value of Islamic education. The purpose of this study was to determine the application of Islamic educational values at SDN Cimanggu 03 Cibungbulang Bogor. This study uses a qualitative method with a phenomenological approach and the data used are the results of interviews, observation, and documentation. The results of this study indicate that: 1) for educational methods that apply Islamic values through exemplary methods, habituation, practice, and advice/initiatives, 2) Islamic value activities carried out are a. celebrating Islamic holidays in the form of Mawlid and Isra Mi'raj, s. attending Islamic boarding schools, c. behave well and politely, d. Visiting friends or teachers affected by the disaster e. Get used to 3S greetings, greetings, and smiles. 3) The formation of the character values of SDN Cimanggu 03 Cibungbulang students takes place in the school environment and in the classroom